The Role of Religious Education in Promoting Interfaith Dialogue in Multicultural Societies - Indriatama Adjani; Fransisca Oktaviani; Nurul Ulfa (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This article explores the role of religious education in fostering interfaith dialogue in multicultural societies. It examines how religious education can cultivate mutual respect, understanding, and cooperation between different religious communities. The study also discusses the pedagogical strategies that can be adopted in religious education to support interfaith dialogue and contribute to social harmony.